German literature of the 1990s and beyond normalization and the Berlin Republic - Taberner, Stuart (Boydell & Brewer, 2005)
This book presents a comprehensive, lively account of recent developments in German fiction at a moment when-for the first time in many years-German authors are once again the subject of international attention and acclaim. It introduces English-speaking audiences to the complex dilemmas that are shaping the ways in which Germans are presently defining themselves, their difficult past, and the new 'Berlin Republic.' The theme that runs throughout the volume is the ongoing debate on German 'normalization.' In offering a wide-ranging consideration of contemporary German literature, the book complements a broad discussion of trends in present-day German politics, society, and culture with detailed readings of texts by internationally renowned figures as W. G. Sebald, Günter Grass, Martin Walser, Marcel Beyer, Ingo Schulze, Judith Hermann, Thomas Brussig, and Bernhard Schlink, and by newer, emerging writers. Topics include the literary debates of the 1990s, the literary market and marketing, literary responses to the former East and West Germany in the age of globalization and to the Nazi past and portrayals of 'ordinary Germans,' depictions of 'German wartime suffering,' contemporary writing on 'Jewish fates' and efforts to revive the 'German-Jewish symbiosis,' and finally, the recent wave of writing about the provinces. Stuart Taberner is a Senior Lecturer in the Department of German at the University of Leeds, UK.
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Geschichte 1900-2000; Geschichte 1990-2004; German literature / 20th century / History and criticism; German literature / 21st century / History and criticism; Deutsch; Literatur; Deutschland; Germany / Intellectual life / 20th century; Germany / Intellectual life / 21st century